English Law and Tadeusz Czacki: Analysis of References to English Legal Sources in Czacki’s Opus Magnum - Cimachowicz, Konrad; Korporowicz, Łukasz Jan (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
Tadeusz Czacki was one of the key figures who participated in the great scholarly discussions about the history, sources of development, and the position of Roman law in old Polish law. The discussion initiated by Czacki and Jan Wincenty Bandtkie in the early years of the nineteenth century lasted for many decades. Its consequences are still present today in modern Polish legal history scholarship. Although Czacki was an author of several legal treatises, most of his pivotal concepts regarding the above-mentioned issues were presented by him in his opus magnum, i.e. O litewskich i polskich prawach, published for the very first time in 1800. Czacki is well known as a self-educated scholar who referred to numerous works, both Polish and foreign. However, the objective of this article is to analyse Czacki’s knowledge and the use of English sources. During the Enlightenment, some Polish intellectuals became fascinated by English culture, politics, and the legal system. The impact of English law, however, has never been analysed in the context of Czacki’s work. The purpose of this article is to fill that gap.